Thermal conductive composites reinforced via advanced boron nitride nanomaterials. (December 2018) - Xu, Chenyang; Miao, Meng; Jiang, Xiangfen; Wang, Xuebin
Abstract: The demand for insulating polymeric composites with high thermal conductivity has increased remarkably for electronic packaging. Since polymers usually suffer from low thermal conductivity, boron nitrides (BN) are emerging as advanced fillers in polymeric composites. BN nanomaterials strikingly reinforce thermal conductivity of polymers and simultaneously improve insulation, thermal expansion, and dielectricity. We herein introduce diverse BN nanomaterials and summarize the progress about thermal conductive composites with various BN fillers from 0D BN particles via 1D nanotubes to 2D nanosheets. 3D fillers, multi-scale and multi-dimensional mixed BN fillers developed recently are also presented. The functionalization and the controlled orientation of fillers are reviewed, and current challenges towards higher thermal conductivity of BN/polymer composites are additionally discussed. Highlights: This review gives an insight into diverse boron nitride nanomaterials which are rising as advanced fillers for polymeric composites. Recent progresses on high-performance thermal conductive composites reinforced by boron nitride are summarized according to dimensionality of fillers.